Financial crises & bank failures in Europe: from bail-outs to bail-ins - Gulamhussen, Azzim (Henry Stewart Talks, 2016)
Why the recent interest in the topic, Pervasiveness of crisis and their inter-relatedness, Evidence from the recent crisis in Europe, From bail-outs to bail-ins, The rationale for resolution and the process, Practicalities of bail-in, Differences with other financial instruments, Going forward with bail-ins